A first-order adaptive solution to rapidly spreading flood waves. (1st January 2013) - Zhang, Chi; Liang, Qiuhua; Yin, Junxian
Aiming to provide accurate and efficient solutions to complex flood waves induced by dam breaks and flash floods, this work introduces a structured adaptive grid based model that solves the 2D shallow water equations using a first-order finite volume Godunov-type scheme. The computational grids dynamically evolves according to the local topographic features, moving wet-dry interfaces and other flow features involving sharp surface gradients. The model is validated against two dam-break benchmark tests with experimental data. The effect of the order of numerical accuracy on the numerical results is also assessed and discussed.